Kelompok Abu Sayyaf dan Radikalisme di Filipina Selatan: Analisis Organisasi Terorisme Asia Tenggara - Adhe Nuansa Wibisono (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2016)
This writing describes a group of Abu Sayyaf (Arabic: Abű Sayyâf, means ‘swordman,’ or ‘father of sword) from its diverse facets: leader and figures, organizational stucture, motive and political ideology, as well as strategy in conducting terrorism actions. Abu Sayyaf is an alias name for the founder, Abdulrajak Janjalani, who is born in Basilan, Philipine. Using an Arabic forename, and Philipine becoming a location for its apearance and establishment, Abu Sayyaf has relation with the struggle of Moro nation, Philipine.